Cushing's syndrome due to a non-adrenal ectopic adrenocorticotropin-secreting Ewing's sarcoma in a child - BEREKET, ABDULLAH; GÜRAN, TÜLAY (My University, 2009)
Ectopic ACTH syndrome (EAS) is extremely rare in the pediatric age group. Sarcomatous tumors causing EAS are even rarer. We report a 9 year-old girl presenting with Cushing's syndrome caused by ectopic ACTH production by a Ewing's sarcoma. This case illustrates that rapid appearance of Cushingoid symptoms, absence of growth retardation and the presence of hypokalemia are suggestive clues for ectopic ACTH production as the source of Cushing's syndrome.
Keywords: Female; Humans; Child; Doxorubicin; Antineoplastic Combined Chemotherapy Protocols; Retroperitoneal Neoplasms; Cyclophosphamide; Vincristine; ACTH Syndrome, Ectopic; Adrenocorticotropic Hormone; Cushing Syndrome; Sarcoma, Ewing